A case study of post traumatic meningitis after a road traffic accident - Satalkar, Durgesh J.; Jaju, Madhusudan R.; Jaya, B. (International Journal of Research in Medical Sciences, 2024)
In road traffic accident cases one of the main reasons for hospitalization is traumatic brain injury (TBI) with subdural hematomas (SDH). The in-hospital course is further complicated by variety of infections including meningitis. A significant concern in the field of bacterial resistance is the multidrug-resistant strain of K. pneumoniae. Due to the dearth of therapeutic options, treating K. pneumoniae infections can be difficult and have an adverse impact on morbidity, mortality, and healthcare-related expenses. Here, we present the case of a 34-year-old polytrauma patient who was in good physical health prior to the road traffic accident. The patient sustained right fronto temporo parietal SDH, frontal contusion, frontal bone fracture, multiple facial bone fracture and CSF rhinorrhoea. He underwent bifrontal craniotomy and ACF repair on the following day. His in-hospital course was complicated by Klebsiella meningitis. He was discharged from the hospital after 25 days of successful treatment of meningitis. In the present study, effective and satisfactory results were achieved through antibiotic therapy which included Colistin IV and intrathecal, Fosfomycin IV, and Tigecycline IV, for a post-operative K. pneumoniae infection. On review day, the CSF analysis had revealed total leucocyte count of 9 and CSF showed no growth.